2018
DOI: 10.1002/celc.201801001
|View full text |Cite
|
Sign up to set email alerts
|

Improved Specific Capacity of Nb2O5 by Coating on Carbon Materials for Lithium‐Ion Batteries

Abstract: Materials for lithium‐ion batteries (LIBs) with excellent electrochemical performance are of significance to meet the increasing demand for rechargeable batteries. Niobium pentoxide (Nb2O5), as an intercalation material with promising electrochemical properties has caught our attention. In this study, Nb2O5 nanoparticles were successfully synthesized through a classical sol‐gel process. The nanoparticles with a size of less than 5 nm were uniformly coated on carbon materials, i. e., reduced graphene oxide (rGO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…[20] Composites with conductive carbons have yielded useful results, where capacities as high as 519 mAhg -1 at 5C were found for a 3D carbon matrix composite. [21] The focus on the T-phase has left the research on the other polymorphs and amorphous phases of Nb 2 O 5 lacking by comparison. The Nb 2 O 5 system is already complex, but synthesis and heat treatment used to yield different polymorphs can also cause differing physical properties within the same polymorph.…”
Section: Fig 1 Polyhedral Views Of the Crystal Structures Of (A) Orth...mentioning
confidence: 99%
“…[20] Composites with conductive carbons have yielded useful results, where capacities as high as 519 mAhg -1 at 5C were found for a 3D carbon matrix composite. [21] The focus on the T-phase has left the research on the other polymorphs and amorphous phases of Nb 2 O 5 lacking by comparison. The Nb 2 O 5 system is already complex, but synthesis and heat treatment used to yield different polymorphs can also cause differing physical properties within the same polymorph.…”
Section: Fig 1 Polyhedral Views Of the Crystal Structures Of (A) Orth...mentioning
confidence: 99%
“…Additionally, the content of Nb2O5 is small, and only extremely weak diffraction peaks of Nb2O5 are detected in the XRD diffraction patterns around 43° and 62°. In addition, as shown in Figure 4B, it can be observed that the 3d3/2, 3d5/2, and 3d5/2 peaks in photoelectron spectroscopy (XPS) are located at 209.9, 207.3 and 207.1 ev, respectively, which belong to Nb2O5 [32,33]. This indicates that Nb2O5 had been effectively coated on the surface of RLM-1.…”
Section: Resultsmentioning
confidence: 85%